Synthesis and Antibacterial Activity of Pyrimidine-2-Thione Derivatives - Barot, V.M.; Modi, S.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Pyrimidine-2-thiones (2a-m) have been prepared by heating chalcone derivatives (1a-m) with thiourea in ethanolic potassiumhydroxide and reacted with chloroacetic acid and acetyl choride yielding the products 3-4.